Adjunctive lacosamide for focal epilepsy: an open‐label trial evaluating the impact of flexible titration and dosing on safety and seizure outcomes. Issue 2 (June 2017) - Baulac, Michel; Coulbaut, Safia; Doty, Pamela; McShea, Cindy; De Backer, Marc; Bartolomei, Fabrice; Vlaicu, Mihaela
Abstract: Aims . To evaluate the safety and effectiveness of lacosamide in a real‐life setting with the use of a flexible dose titration schedule and individualised maintenance doses up to the maximum approved dose of 400 mg/day. Methods . Adults with a diagnosis of focal seizures, with or without secondary generalization, were enrolled in this open‐label Phase IV trial (NCT01235403). Lacosamide was initiated at 100 mg/day (50 mg bid) and uptitrated over a 12‐week period to 200, 300 or 400 mg/day, based on safety and seizure control. Although dose increases were to be in increments of 100 mg/day, intermediate doses were permitted at each escalation step for one week for patients known to be particularly sensitive to starting new AEDs. After receiving a stable, effective dose for three weeks, patients entered the 12‐week maintenance period. Primary outcomes were incidence of treatment‐emergent adverse events (TEAEs) and withdrawal due to TEAEs. Seizure outcomes, all secondary, were median focal seizure frequency, ≥50% reduction in focal seizure frequency, and seizure freedom. Results . One hundred patients with a mean age of 44 years were enrolled and 74 completed the trial. The incidence of TEAEs was 64.0% ( n =100), with the most frequently reported (≥5% of patients) being dizziness, headache, and asthenia. Fourteen patients withdrew due to TEAEs, most frequently due to dizziness (six patients; 6.0%), vomiting (two patients; 2%), and tremor (two patients; 2%). Among patients with baseline and maintenance phase seizure data ( n =75), median reduction in focal seizure frequency from baseline was 69.7% and the ≥50% responder rate was 69.3%. Among 74 patients who completed the maintenance phase, 21 (28.4%) were seizure‐free. Conclusion . Flexible lacosamide dosing in this open‐label trial was associated with a favourable tolerability and safety profile; the nature of the TEAEs was consistent with that observed in previous pivotal trials. Treatment with lacosamide was also associated with effective seizure control.